Heat transfer characteristics of gas-liquid two-phase flow in microtubes - Lim, Yau Shiang (2014)
It is well-known that microelectronic devices would generate high heat fluxes. Given the same heat flux generated, smaller size means more concentration of heat at one particular area. Hence, efficient thermal management is required for these devices to ensure the effective operations of these devices. Heat dissipation via microchannels has been considered as an effective method for removal of high heat fluxes due to its high surface to volume ratio.